Perbedaan Tingkat Kecemasan Ibu Bersalin Pada Kelas Ibu Hamil Di Wilayah Kerja Puskesmas Tulung - Intan Nugraheni; Kuswati Kuswati (Poltekkes Kemenkes Surakarta, 2017)
Abstract: Class Pregnant Women; Levels Of Anxiety. Anxiety is one of the main factors that influence whether or not an action smoothness of delivery. Pregnant women with sufficient knowledge proved to have a low risk of the occurrence of complications of childbirth. Educational intervention in the form of counseling mothers on maternal class. Purpose is to knowing the differences in levels of maternal anxiety on the class of pregnant woman in the Puskesmas Tulung. Type of quasi-experimental research design with a static group comparison. The population is pregnant women PHC Tulung region. Samples are 36 pregnant women who meet the criteria cadre, which consisted of 18 pregnant women who attend classes pregnant women and 18 pregnant women who donot attend classes pregnant women with purposive sampling technique. Respondents who attend classes maternal anxiety has a value of at least 6, the maximum value of 20 with an average of 15.4 and the majority of respondents (61.1%) had anxiety medium category. Those who do not attend classes anxiety mother has a value of at least 14, the maximum value of 27, with an average of 20.67 and a majority of respondents have anxiety was (88.9%). There are differences in the level of maternal anxiety that follows and that pregnant women do not attend classes in the Puskesmas Tulung, with significant differences in anxiety score (p value = 0.000).